Pengaruh Pemberian Jus Buah Sirsak (Annona Muricata Linn) Terhadap Kadar Malondialdehyde (MDA) Plasenta Tikus Putih Strain Wistar (Rattus novergicus) Bunting dengan Paparan Asap Rokok) - Nurdiana Zaenal; Novida Ariani; Intan Zahiroh (Jurnal Multidisiplin Madani, 2022)
Cigarettes contain many toxic free radicals and reactive oxygen species (ROS) which can trigger cell membrane lipids, proteins, enzymes, and DNA to undergo oxidative damage. The amount of ROS (reactive oxygen species) during pregnancy can increase if pregnant women are exposed to cigarette smoke which are toxic due to the risk of oxidative stress so as to form Malondialdehyde (MDA) compounds caused by lipid peroxidation. Lipid peroxidation and increased levels of MDA can cause damage to cell membranes, one of which is the placental endothelial cell membrane. The content of vitamin C and sufficient polyphenols in soursop has the potential as a source of antioxidants that can inhibit or slow down the formation of free radicals and ROS. Objective: To determine the benefits or effect of giving soursop fruit juice (Annona muricata Linn) on the placental MDA levels of pregnant rats with wistar strain (Rattus norvegicus) exposed to cigarette smoke. Methods: A true experimental laboratory with a randomized posttest-only control group design. Different doses of exposure to cigarette smoke and soursop juice were selected at random and divided into 3 treatment groups and 2 control groups. Giving soursop fruit juice was carried out on the first day until the nineteenth day of pregnancy, while cigarette smoke was exposed on the seventh day until the nineteenth day of pregnancy. Results: The significance value calculated by the Kruskal-Wallis test was 0.350 (p>0.05), which showed that there was no significant effect on the MDA value of the placenta of pregnant rats given soursop fruit juice and exposed to cigarette smoke. Conclusion: Soursop fruit juice with a dose of 0.5gr/200gr BW/day can prevent the increase in MDA levels of pregnant rat placenta exposed to cigarette smoke.